PROFESSIONAL MOBILITY OF A SOFTWARE ENGINEER: THE DEFINITIVE ANALYSIS - Теремінко, Л. Г. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article analyzes the results of theoretical studies of the psychological and pedagogical concept of «professional mobility» by domestic and foreign scientists. It covers main approaches to the specified concept. The urgency of professional mobility for professional activities of any specialist, particularly a software engineer is proved. Based on the analysis of software industry employers’ requirements to professional and personal qualities of applicants for vacant posts, the definition of «professional mobility of a software engineer» is given. We treat professional mobility of these professionals as the integrative quality of personality, which is readiness and ability to adapt to constantly changing conditions of professional activities, the ability to switch between different methods and technologies of software development and implementation, readiness to perform different duties within professional activity, to constant self-education and self-improvement